STORE LAYOUT FOR VIRTUAL RETAILING: A LITERATURE REVIEW - Masudin, Ilyas; Fuadi, Mukhlish (Jurnal Ilmiah Teknik Industri, 2014)
The progress of online shopping worldwide has impacted significantly to business processes as well as customers? behavior in shopping. Thus, research in online retailing especially in virtual store layout has been made by researchers in numerous numbers. This article attempts to explore prior research in virtual layout retails to identify the research in virtual retailing in term of the variables involved in designing the virtual store layout.